Global health and human rights in the time of COVID-19: Response, restrictions, and legitimacy. Issue 5 (19th October 2020) - Forman, Lisa; Kohler, Jillian Clare
Abstract: Policy responses to the COVID-19 pandemic have impacted a range of human rights, with the pandemic being used to justify police violence, authoritarian power grabs, and corruption. Health systems in high- and low-income countries have struggled to provide adequate COVID-19 testing, tracing, and treatment, with non-COVID-19 healthcare-restricted, vulnerable populations at high risk of infection and negative health and social impacts, and lockdowns exacerbating poverty, domestic violence, and mental health problems. If underresourced health systems are overwhelmed by COVID-19, and individuals are forced to bear testing and treatment costs, there is a stronger likelihood of health system failures, for higher mortality from a range of causes, and for people to be pushed further into poverty and insecurity. COVID-19 thus underscores the urgent need for clearer rules about legitimate restrictions of the right to health in responding to the pandemic, and for safeguarding global health policy initiatives in its aftermath. This article focuses on key right-to-health challenges, including realization of universal health coverage, and potential challenges in access to future COVID-19 therapies and vaccines. We conclude with reflections on what the pandemic may mean for the evolution of human rights, and the right to health in particular.